Home Based Cardiac Rehabilitation in Cardiovocal Syndrome - Manuaba, Ida Ayu Wulan Kartika Dewi; Dharma, Bagus Diva Indra; Silakarma, Dedi (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Cardiovascular disease is one of the highest causes of death and disability in the world. Cardiac Rehabilitation has an important role in the management of patients with heart diseases. This article reported a Cardiac Rehabilitation for a 22-year-old male patient with Cardiovocal Syndrome, a rare condition characterized by heart failure accompanied by hoarseness. The Cardiac Rehabilitation in this case was a phase 2 Cardiac Rehabilitation that carried out as Home based Cardiac Rehabilitation. We performed the 6MWT for the patient to assess his physical endurance. After 3 months of Cardiac Rehabilitation program, patient has physical endurance was improved, his voice was back to normal and he was able to return to work.